Pengaruh Ukuran Perusahaan dan Profitabilitas pada Ketepatwaktuan Penyampaian Laporan Keuangan dengan GCG Sebagai Variabel Pemoderasi - Yasinta Darmawan, Gusti Ayu Putu; Dwiana Putra, I Made Pande (E-Jurnal Akuntansi; Vol 25 No 1 (2018)DO - 10.24843/EJA.2018.v25.i01.p20, 2018)
This study aims to prove empirically the influence of company size and profitability on timely delivery of financial statements with good corporate governance as a moderator variable. This study was conducted on non-financial public and go public companies listed in the 2011-2015 Corporate Governance Perception Index (CGPI) assessment. The method of determining the sample used is to use purposive sampling. The number of companies that meet the criteria is 9 companies with a total number of 43 observations. Data collection was done by non participant observation method. By using Multiple Regression Test and Moderated Regression Analysis (MRA), it was found that firm size did not affect the timeliness of financial statement submission but profitability had an effect on the timeliness of financial statement submission. The study also found that good corporate governance is not able to moderate the influence of firm size on the timeliness of financial statement submission but able to moderate by weakening the influence of profitability on timely delivery of financial statements Keywords :  Timeliness of Financial Report Submission, Company Size, Profitability, Good Corporate Governance